3D DNA nanostructure : methods and protocols - Ke, Yonggang; Wang, Pengfei (Methods in molecular biology, 2017)
This detailed volume presents a comprehensive technical overview of DNA nanotechnology with an emphasis on 3D DNA nanostructure design and applications. Coverage spans from basic design principles for DNA and RNA nanostructures to their cutting-edge applications in a variety of fields, with the book divided into basic DNA and RNA nanostructure design strategies as well as applications utilizing DNA nanostructures, including but not limited to nanomedicine, bioimaging, biosensing, nanoplasmonics, nanoelectronics, nanofabrication, crystallography, biophysics, and analytical chemistry. Written for the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Comprehensive and authoritative, 3D DNA Nanostructure: Methods and Protocols provides the most up-to-date tutorial style overviews and technical style protocols to benefit researchers in a wide variety of areas.--